2015
DOI: 10.15361/2175-0106.2015v31n2p100
|View full text |Cite
|
Sign up to set email alerts
|

Primeiro Surto De Tripanossomose Bovina Detectado No Estado De Goiás, Brasil

Abstract: RESUMOEste trabalho objetivou relatar o surto de tripanossomíase no estado de Goiás, evidenciando a importância da profilaxia desta doença infectocontagiosa. O surto ocorreu em uma propriedade rural próximo ao município de Ipameri -GO. Com 160 animais no rebanho, o proprietário adquiriu mais 18 animais Girolando de origem desconhecida. Dezesseis dias após a aquisição destes animais, três deles apresentaram decúbito. Observou-se queda de 25% na produção de leite no 20º dia após a compra. Seis animais morreram n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Nesse ínterim, ocorre a transmissão da doença por meio do contato diário constante entre animal e animal (vacas no confinamento nos currais), humano e animal (no momento da ordenha) e/ou vice-versa (RADOSTITS et al, 2007), como também por meio de fômites con- taminados, por exemplo, o uso de ocitocina para ejeção de leite, havendo compartilhamento de uma mesma agulha com diferentes animais, onde facilita a disseminação de doenças das vacas infectadas para sadias (BASTOS et al, 2013;BARBOSA et al, 2015).…”
Section: Resultsunclassified
“…Nesse ínterim, ocorre a transmissão da doença por meio do contato diário constante entre animal e animal (vacas no confinamento nos currais), humano e animal (no momento da ordenha) e/ou vice-versa (RADOSTITS et al, 2007), como também por meio de fômites con- taminados, por exemplo, o uso de ocitocina para ejeção de leite, havendo compartilhamento de uma mesma agulha com diferentes animais, onde facilita a disseminação de doenças das vacas infectadas para sadias (BASTOS et al, 2013;BARBOSA et al, 2015).…”
Section: Resultsunclassified
“…It was suggested that the protozoan was introduced through the acquisition of animals with subclinical infection, acquired without examination and Advances in Animal and Veterinary Sciences June 2020 | Volume 8 | Issue 6 | Page 631 prior knowledge of their health status. The movement and commercialization of animals in the absence of adequate sanitary control is one of the most important risk factors for the occurrence of outbreaks of the disease as well as for its spread (Barbosa et al, 2015). In addition, the incidence of the disease probably increased within the property, through the use of shared needles, especially during the injection of the hormone, oxytocin, which is used to help eject milk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence of the disease probably increased within the property, through the use of shared needles, especially during the injection of the hormone, oxytocin, which is used to help eject milk. Barbosa et al (2015) reported the relationship between outbreaks in Goiás, and the daily administration of oxytocin in cows, intravenously, before milking, using the same needle and syringe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation